A comparative life cycle study of alternative materials for Australian multi-storey apartment building frame constructions: Environmental and economic perspective. (10th November 2017) - Lu, Hangyong Ray; El Hanandeh, Ali; Gilbert, Benoit P.
Abstract: The building construction sector contributes to a quarter of the total Australian Greenhouse gas emissions. These emissions are mainly attributed to the use of energy intensive materials. To achieve better environmental benefits and cost saving, the utilisation of wood-based construction materials is currently attracting attention. However, the manufacturing of engineered wood products consumes large quantities of chemicals and energy, which may have adverse environmental impacts. Therefore, a life cycle study was conducted to compare various materials for constructing the structural frame of a 4-storey apartment building compliant with the Australian building codes. Five alternatives were assessed: Laminated Veneer Lumber (LVL) manufactured from early to mid-rotation hardwood plantation logs (LVLm ), LVL manufactured from mature hardwood plantations (LVLh ), LVL manufactured from mature softwood plantations (LVLs ), concrete and steel. The functional unit was defined as the whole building structural frame. Global Warming Potential (GWP), Acidification, Eutrophication, Fossil Depletion, Human-toxicity Potential (HTP) and Life Cycle Cost (LCC) were evaluated. The LVL generally performed better than concrete and steel structural products. Particularly, LVLm had the lowest GWP (2.84E4±233 kg-CO2-eq ) and LCC ($128, 855 ± 2797), which were less than a quarter of the concrete option. However, the usage of chemical preservatives and phenol-formaldehyde adhesive during the LVL production and treatment caused the HTP impact to be higher than the steel option. Monte Carlo Analysis showed that while the LVL options presented a higher sensitivity to the combined uncertainties, the overall ranking of the five options remained the same. Therefore, the inclusion of wood-based material in structural elements may significantly contribute to reduce the environmental impacts and the LCC of the construction sector. Highlights: Five alternatives for multi-storey residential building frame construction were assessed. Life cycle assessment and life cycle costing analysis were conducted. Low material cost and labour demand led to economic saving in the LVL options. Chemical consumption was a major contributor to the environmental impacts of LVL. LVL from hardwood thinning had the best environmental and economic performance.